The changing face of African farmland in an era of rural transformation - Jayne, Thomas S.; Muyanga, Milu; Wineman, Ayala; Ghebru, Hosaena; Stevens, Caleb (Michigan State University, 2019)
Mounting evidence suggests that sub-Saharan Africa has undergone profound rural transformation since the early 2000s, though progress has been highly uneven across countries. Conventional views of African agriculture are in many respects becoming obsolete. Our review highlights the evidence of farm-level transformation in the region, identifies the key sources of dynamism in the sector, and proposes an updated typology of farms that reflects the evolving nature of African agriculture. We underscore the rising importance of an entrepreneurial class of African commercialized medium-scale farmers, and examine the causes and consequences of this phenomenon.